Increasing Financial Management Capabilities at MSMEs - Malang Meatballs - Octaviani, Haniifah; Rachman, Cinta Chantika Suryana (prodima@fe.uika-bogor.ac.id, 2023)
Interview observation activities with MSME traders conducted by fe-male students from the University of Buana Perjuangan Karawang have given questions to one of the Micro, Small and Medium Enterpris-es (MSMEs), especially in Karawang City, namely the Bakso Malang company. This business has branches and one of its marketing areas is Citra Kebun Mas Housing, Karawang. This business is a very popular food for the people of Indonesia, the product categories sold are meat-balls, egg meatballs, plain chicken noodles, small chicken meatball noo-dles, chicken meatball noodles, chicken egg meatball noodles. the pur-pose of this study was to determine the increase in financial manage-ment capabilities in UMKM - Bakso Malang. This research was con-ducted on March 29 2023 at Citra Kebun Mas Karawang Housing Complex. This type of research is descriptive. The results of the study show that generally MSME meatball owners in the Karawang city area do not have adequate financial knowledge. There are still obstacles for business people in terms of knowledge and awareness to keep records and financial reports. Business people tend to think that only by collect-ing proof of transactions and keeping records. Therefore, many MSME sellers do not make financial reports because they are considered to be costly and time consuming.